A review on solar energy use in industries - Mekhilef, Saad; Saidur, Rahman; Safari, Azadeh (Elsevier, 2011)
Presently, solar energy conversion is widely used to generate heat and produce electricity. A comparative study on the world energy consumption released by International Energy Agency (IEA) shows that in 2050, solar array installations will supply around 45 of energy demand in the world. It was found that solar thermal is getting remarkable popularity in industrial applications. Solar thermal is an alternative to generate electricity, process chemicals or even space heating. It can be used in food, non-metallic, textile, building, chemical or even business related industries. On the other hand, solar electricity is wildly applied in telecommunication, agricultural, water desalination and building industry to operate lights, pumps, engines, fans, refrigerators and water heaters. It is very important to apply solar energy for a wide variety of applications and provide energy solutions by modifying the energy proportion, improving energy stability, increasing energy sustainability, conversion reduction and hence enhance the system efficiency. The present work aimed to study the solar energy systems utilization in industrial applications and looked into the industrial applications which are more compatible to be integrated with solar energy systems.